Enchâssement des voix et requalification de l’expérience dans l’œuvre polyadressée de Manuela Draeger - Florence Traisnel (Strenae)
Post-exoticism, founded by Antoine Volodine, presents itself as a vast system of texts written by an imaginary collective of incarcerated writers. This subversive literary enterprise is carried out by many voices. One of them, a woman, is particularly aimed at a youth readership. Reading Manuela Draeger's children’s stories in the light of Walter Benjamin's "The Storyteller" brings to light the improbable weaving of these two modes of speech, that of the tale, and that of the novel, which, despite the philosopher’s opposition, Draeger nevertheless pulls together. Through a subtle and dizzying game of entanglement, Draeger recasts the Erlebnis novels into Erfahrung tales, while thrusting to the forefront the multiple identities of the storytellers, whose voices take turns in echoing these shared stories.